2019
DOI: 10.1177/1687814019848272
|View full text |Cite
|
Sign up to set email alerts
|

Traffic impacts analysis of bus stops near signalized intersections based on an optimal velocity model

Abstract: The aim of this study is to investigate the impact of the bus stop near the signalized intersection on the traffic flow from two aspects, traffic volume and delay. A modified Optimal Velocity model is established to analyze the dynamic traffic flow near a signalized intersection with curbside bus stops, and two cases including bus stops placed upstream and downstream the intersection are simulated to compare the impacts. The influencing factors, including the entering probability and the distance between a bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…On-street parking manoeuvres can often block traffic for short time causing temporary bottlenecks [43] or sometimes create start-stop traffic flow behaviour on the lanes adjacent to the parking lane [44] and can reduce the road capacity by 20-30% [45]. Some studies have also analysed the impacts of roadside bus stops, which can also disrupt the traffic flow at signalized intersections [46,47]. Buses dwelling at the bus stops to load and unload passengers may occupy a portion of a traffic lane or a bus bay and while moving into or out of the bus stop can block the traffic flow on the adjacent lane, causing excessive delays to the road users and reduction in the capacity of the intersection [13,[48][49][50].…”
Section: Incident Types and Durationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On-street parking manoeuvres can often block traffic for short time causing temporary bottlenecks [43] or sometimes create start-stop traffic flow behaviour on the lanes adjacent to the parking lane [44] and can reduce the road capacity by 20-30% [45]. Some studies have also analysed the impacts of roadside bus stops, which can also disrupt the traffic flow at signalized intersections [46,47]. Buses dwelling at the bus stops to load and unload passengers may occupy a portion of a traffic lane or a bus bay and while moving into or out of the bus stop can block the traffic flow on the adjacent lane, causing excessive delays to the road users and reduction in the capacity of the intersection [13,[48][49][50].…”
Section: Incident Types and Durationsmentioning
confidence: 99%
“…where T is the time required for the Nth vehicle in the queue to cross the stop-line, L is the start-up lost time, and h is the saturation headway in seconds. e values [37] Disabled vehicles, abandoned vehicles, debris, and others Clearance time-13 minutes Chavis and Christofa [48] Bus stop Dwell time-40 seconds (mean); 30 seconds (standard deviation) Ghasemlou et al [50] Bus stop Dwell time-20, 30, and 40 seconds Liang and Ma [46] Bus stop Dwell time-10 to 20 seconds Liu and Jian [47] Simulated incident-bus stop Dwell time-35 to 55 seconds Cao and Menendez [43] Parking manoeuvre Incident duration-2 to 32 seconds of L and h are to be calibrated in advance for any intersection.…”
Section: Incidents' Occurrence and Clearance Identificationmentioning
confidence: 99%
“…In general, the location of bus stops requires special attention when justifying the method of public transport prioritization. Depending on their location relative to intersections and the sections of streets between them, the regularities of delays in the movement of both public and private transport may change [16][17][18]. Based on the analysis of these studies, the location of a stopping point before the intersection is a better solution than after it but only for distances within 70-200 m. Along with this, in the studies [16,17], it is noted that with such a solution the number of delays at the stopping point will be relatively insignificant when the volume of public transport traffic is up to 200 p.c.u./h.…”
Section: Introductionmentioning
confidence: 99%
“…Several features affect the service such as the stop design that has a significant impact on transit vehicle, on the operations of the intersection and its safety as well as the adjacent properties and the system performance (Transit Cooperative Research Program, 1996). The bus stop location, which can be either before near-side or far-side, the design can have an impact on the traffic as some studies have found that the farside stops encounter less overall delays, while the near-side stop may cause more issues (Liu and Jian, 2019).…”
Section: Introductionmentioning
confidence: 99%